Maternal chitosan oligosaccharide supplementation during late gestation and lactation optimizes placental function in sows and intestinal function in 21-day-old IUGR suckling piglets - Wang, Xintao; Fang, Tingting; Chen, Daiwen; Pu, Junning; Tian, Gang; He, Jun; Zheng, Ping; Mao, Xiangbing; Wu, Aimin; Yu, Bing (Frontiers in Veterinary Science, 2024)
Maternal dietary supplementation with chitosan oligosaccharide (COS) has been considered as a potential intervention to mitigate the occurrence of intrauterine growth restriction (IUGR) and improve postnatal growth. The present study investigated the effect of COS as a dietary supplement for sows during late gestation and lactation on their productivity, placental function, and the intestinal health of IUGR piglets. From day (d) 85 of late gestation to d 21 of lactation, 30 sows were randomly divided into either a control group (basal diet) or a COS group (basal diet + 100 mg kg−1 COS). At d 21 of lactation, eight normal and eight IUGR littermates from eight litters belong to control sows, as well as eight IUGR littermates from COS sows, were selected for further analysis. The results showed a significant reduction in the number of stillbirths and mummies in COS groups (p < 0.05). Maternal dietary supplementation with COS also significantly up-regulated the expression levels of GLUT1, GLUT3, and VEGFA mRNA in the placenta of IUGR piglets compared to those in control group (p < 0.05). Furthermore, there was a significant decrease in MDA content and a significant increase in GSH content in the placenta of IUGR piglets from COS sows compared to those from control group (p < 0.05). Additionally, the expression levels of MUC2 and occludin mRNA as well as claudin1 protein significantly up-regulated in the jejunum of 21-day-old IUGR piglets from COS sows group compared to those from control group (p < 0.05). Moreover, IL-10 mRNA expression level was significantly increased while MDA content was significantly reduced in the jejunum of 21-day-old IUGR piglets from COS sows group compared to those from control group (p < 0.05). The results indicated that maternal dietary COS supplementation during late gestation effectively reduced the incidence of stillbirths and mummies, potentially linked to enhanced placental function, reduced oxidative stress, and improved immune status. Furthermore, maternal dietary COS supplementation exhibited positive impact on intestinal digestive and absorptive function, intestinal barrier integrity, intestinal antioxidant capacity and immune status in 21-day-old suckling IUGR piglets.